Validation and establishment of cell culture models to study invasion and feto-maternal interaction in the bovine placentome - Bridger, Philip Simon; Justus Liebig University Giessen (My University, 2008)
A unique feature of bovine synepitheliochorial placenta is the occurrence of restricted trophoblast invasion characterized by the migration and fusion of trophoblast giant cells (TGC) with single maternal epithelial cells. Unlike tumor invasion, this process is limited to the depth of the caruncular epithelium suggesting the bovine placenta to be an ideal model to study mechanisms regulating cellular invasion. In-vitro models of the reproductive tissues involved are lacking though these models would also allow the assessment of pathogenesis of pregnancy-associated diseases und thus reduce the number of animal experiments. The thesis presented discusses an interconnection of three articles published in peer reviewed journals ([1] Theriogenology, 2007; 68 (4):592-603; [2] Placenta, 2007; 28 (11-12):1110-1117; [3] Biology of Reproduction, 2008; in press) focusing on the characterization and functional assessment of primary caruncular epithelial cells as well as the development of a cell line. Primary caruncular epithelial cells were successfully isolated and cultured from manually separated caruncles from the third month of gestation onwards. Fluorescence in-situ hybridization (FISH) not only confirmed the maternal origin of these cells but also demonstrated a contamination of cotyledonary-derived cultures with maternal epithelial cells. An extensive phenotypic and functional characterization defined these cells to be of epithelial origin forming an intact epithelial monolayer in culture. The cells grew as a monolayer, and via transmission and scanning electron microscopy a polarized morphology with apical microvilli and junctional complexes was demonstrated. Expression of epithelial-specific cytokeratin and Zonula occludens-1 protein as well as vimentin but not alpha-smooth muscle actin and desmin was shown by immunofluorescence. Furthermore, transepithelial electrical resistance measurements (TEER) of cultures grown on Transwell® inserts confirmed the presence of an intact epithelial barrier. The expression and co-localization of integrin subunit beta1 and associated signaling molecules (alpha-actinin, focal adhesion kinase, phosphotyrosine and talin) showed that caruncular epithelial cells actively participate in integrin-mediated inside-out and outside-in signaling pathways. Culture on dishes coated with proteins of the extracellular matrix, fibronectin in particular, resulted in increased proliferation and enhanced the expression of integrin and integrin-associated signaling molecules. By continuous subculture and spontaneous immortalization of the first caruncular epithelial cell line (BCEC-1) derived from a pregnant cow was established. The cells maintained their epithelial properties as shown for primary cells for up to 32 passages. In addition, the cells were tested negative for the BVDV but remained susceptible to infection. In order to introduce this model for commercial use (i.e. screening essays), BCEC-1 has been patented (PCT/DE 2007 001274). In conclusion, the thesis demonstrates the importance of appropriate cell characterization and identification especially when cells are isolated from epitheliochorial placentae. The phenotypic and functional properties of primary caruncular epithelial cells and BCEC-1 suggest that both models provide excellent potential for further functional studies, i.e. co-culture invasion assays as well as the physiology and pathology of feto-maternal interaction and pregnancy-associated diseases. In-vitro models, cell cultures in particular cannot completely replace experiments in-vivo however may be more efficient in generating preliminary results, and subsequently less animal experiments will be required. Supported by a grant of the German Research Foundation (DFG).

Eine Besonderheit der bovinen synepitheliochorialen Plazenta ist die eingeschränkte Trophoblastinvasion, die durch migrierende Trophoblastriesenzellen (TGC) charakterisiert ist, welche jeweils mit einer einzelnen maternalen Epithelzellen fusionieren. Im Gegensatz zur Tumorinvasion ist die Trophoblastinvasion gerichtet und ausschließlich auf das karunkuläre Epithel beschränkt. Daher ist es naheliegend die bovine Plazenta als Modell zur Untersuchung von zellulären Invasionsmechanismen zu verwenden. Bislang gibt es jedoch keine geeigneten in-vitro Modelle aus den Geweben, die an der Trophoblastinvasion beteiligt sind. Derartige Modelle würden auch Studien zur Pathogenese Trächtigkeits-assoziierter Erkrankungen ermöglichen und somit auch zur Reduktion von Tierversuchen beitragen. Diese kumulative PhD-Arbeit diskutiert drei begutachtete und publizierte Manuskripte ([1] Theriogenology, 2007; 68 (4):592-603; [2] Placenta, 2007; 28 (11-12):1110-1117; [3] Biology of Reproduction, 2008: in press), die sich schwerpunktmäßig mit der Charakter-isierung und funktionellen Untersuchung von primären bovinen Karunkelepithelzellen sowie der Etablierung einer Zelllinie befassen. Primäre Karunkelepithelzellen wurden erfolgreich aus manuell separierten Karunkeln (3.-9. Trächtigkeitsmonat) isoliert und kultiviert. Die maternale Herkunft dieser Zellen sowie die Kontamination primärer kotyledonärer Kulturen mit maternalen Zellen wurden mittels Fluoreszenz in-situ Hybridisierung gezeigt. Eine umfangreiche phänotypische und funktionelle Charakterisierung bestätigte die epitheliale Herkunft der Zellen sowie die Ausbildung einer intakten epithelialen Barriere in-vitro. Mittels Transmissions- und Raster-elektronenmikroskopie konnte die epithelspezifische polarisierte Morphologie mit apikalen Mikrovilli und Schlussleistenkomplexen des zellulären einschichtigen Zellrasens gezeigte werden. Die Immunfluoreszenz ergab, dass die Zellen epitheliales Zytokeratin und Zonula occludens-1 Protein aber auch Vimentin exprimierten. Dagegen bilden die Zellen kein alpha-smooth muscle Aktin und Desmin aus. Messungen des transepithelialen Widerstandes konfluent wachsender Zellen, die in Transwell® inserts kultiviert wurden, zeigten das Vorhandensein einer intakten epithelialen Barriere. Die Expression und Kolokalisation der Integrin Untereinheit beta1 und Integrin-assoziierten Signalmolekülen (alpha-Actinin, Focal Adhesion Kinase, Phosphotyrosin und Talin) zeigte, dass Karunkelepithelzellen in-vivo und in-vitro aktiv an Integrin-vermittelten outside-in und inside-out Signalwegen beteiligt sind. Das Kultivieren der Zellen in mit Proteinen der extrazellulären Matrix (Fibronectin im Besonderen) beschichteten Gefäßen, beschleunigte die Zellproliferation und erhöhte die Expression von Integrin beta1 und dessen assoziierten Signalmolekülen. Durch fortwährende Subkultivierung und der daraus resultierenden spontanen Immortalisierung konnte die erste bovine Karunkelepithelzelllinie (BCEC-1) aus einem trächtigen Tier generiert werden. Die Zellen behielten ihre epithelialen Eigenschaften bis zur 32. Passage bei. Weiterhin wurden die BCEC-1-Zellen negativ für das Vorhandensein des BVD Virus getestet. Andererseits konnten die Zellen mit dem Virus infiziert werden. Um BCEC-1 dem kommerziellen Gebrauch anzubieten, wurden verschiedene Anwendungsmöglichkeiten patentiert (PCT/DE 2007 001274). Schlussfolgernd zeigt diese Arbeit die Bedeutung einer adäquaten Charakterisierung und Identifizierung von Zellen, vor allem wenn diese aus epitheliochorialen Plazenten isoliert werden. Die phänotypischen und funktionellen Eigenschaften von primären Karunkel-epithelzellen und BCEC-1 stellen ein hervorragendes Potential für zahlreiche weitere Studien dar. Dazu könnten Kokultur-Invasionsassays und Modelle zur Untersuchung der Physiologie und Pathologie Trächtigkeits-assoziierter Erkrankungen zählen. In-vitro Modelle, Zellkulturen im Besonderen, können Tierversuche nicht vollständig ersetzten. Dennoch sind sie in der Generierung vorläufiger Ergebnissen sehr effizient. Diese wiederum könnten unnötige Tierversuche vermeiden. Diese Arbeit wurde durch die Deutsche Forschungsgemeinschaft (DFG) gefördert.
Keywords: ddc:630